Students habits and academic performance among students in UiTM Pasir Gudang - Dzulkifli, Siti Khadijah; Abdul Latif, Mariatul Qabtiah; Nazaruddin, Nanie Khairiena; Kila, Nur Awatif; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Academic performance refers to a student's level of achievement in their educational endeavours. The evaluation of education quality in universities often relies on students' academic performance, which is influenced by various factors, including study habits. Study habits refer to individual behaviours and skills related to studying, encompassing study methods that enhance motivation and facilitate effective learning. These habits are crucial for achieving success and differ from person to person. The connection between student behaviour and academic achievement has been extensively studied. Studies consistently show that good habits, such as positive habits like effective time management and active engagement in learning, lead to better academic outcomes. The objective for this study is to examine the relationship between study habits and the academic achievement of students at UiTM Pasir Gudang, Johor (UiTM). From the study, in can be concluded that study habits give a big contribution to the academic performance. Most of respondents like to study in calm and peaceful environment without any disruptions from outside world especially hand phone. This condition lead to a better performance in their academic.